2014
DOI: 10.1017/s095442241400016x
|View full text |Cite
|
Sign up to set email alerts
|

Twin studies advance the understanding of gene–environment interplay in human nutrigenomics

Abstract: Investigations into the genetic architecture of diet-disease relationships are particularly relevant today with the global epidemic of obesity and chronic disease. Twin studies have demonstrated that genetic makeup plays a significant role in a multitude of dietary phenotypes such as energy and macronutrient intakes, dietary patterns, and specific food group intakes. Besides estimating heritability of dietary assessment, twins provide a naturally unique, case-control experiment. Due to their shared upbringing,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 97 publications
0
9
0
Order By: Relevance
“…Like VFM, 54 we found this score to be strongly determined by genetics ( h 2 : 44%), which agrees with previous findings where the heritability of ‘unhealthy’ diet patterns ranged from 33 to 50%. 55 The limitations of our study also warrant discussion. First, our population was predominantly female and therefore, our results may not apply to men.…”
Section: Discussionmentioning
confidence: 85%
“…Like VFM, 54 we found this score to be strongly determined by genetics ( h 2 : 44%), which agrees with previous findings where the heritability of ‘unhealthy’ diet patterns ranged from 33 to 50%. 55 The limitations of our study also warrant discussion. First, our population was predominantly female and therefore, our results may not apply to men.…”
Section: Discussionmentioning
confidence: 85%
“…Accounting for these confounding genetic effects and additionally many shared environmental and cohort effects provides significantly greater power than other study designs (Rakyan et al, 2011), and these combined numbers across the consortium will enable rigorous replication of small scale positive findings, as well as novel discoveries to be made. Many other omics technologies may be applied to disease discordant twins (metabolomics, transcriptomics, glycomics, metagenomics, proteomics), providing a complete picture of the processes involved in disease development and progression (Pallister et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Findings from twin studies have indicated that genetics plays a major role in several diet-related phenotypes including energy and macronutrient intakes, dietary patterns, and the intake of specific foods [28]. Twins provide a naturally unique case-control experiment whereas the classical twin design compares the similarity of identical/monozygotic (MZ) and dizygotic (DZ) twins.…”
Section: Introductionmentioning
confidence: 99%